HAK NAFKAH ISTRI YANG BEKERJA MENURUT PANDANGAN KIAI KRAPYAK - Yuniar Ihsanul Alfan (Fakultas Syariah (Syari'ah Faculty ), 2020)
Before the existence of Law number 41 of 2004 concerning endowments, Indonesia has a Government Regulation number 28 of 1977 on the ownership of privately owned land, which was subsequently changed by the Compilation of Islamic Law (KHI) until finally result in Law number 41 of 2004. Along with the development, also develops problems that arise around waqf, one of which is the withdrawal of waqf by waqf heirs. In this study the authors refer to the views of the jurists, namely the views of Imam Malik and Imam Asy-Shafi’i. the research method used is comparative analytic descriptive. From the result of the study indicate that the opinion of Imam Malik waqf property is still in the hands of giver, it means that the recipient of the waqf does not have the rights to the goods or property (waqf) give, because according to him waqf is just a release of benefits. In contrast to the opinion of Imam Shafi’i showing that the property or objects as well as the benefits of the assets that have been represented have been completely separated from wāqif.